The Wish to Cure and the Curiosity to Investigate – Or How I Used My Life to Become a Physician-Scientist - Fries, Jochen Walter Ulrich (Frontiers in Medicine, 2015)
Abstract The author describes how he became a physician-scientist: difficulties he had to overcome coming from outside of the US (visa, funding, resident training), while experiencing the thrill of actively particiating in moving science. Setbacks, scientific success, adaptation to new developments, and the encounter of kindred spirits characterise this lifelong effort.